Influence of seed rates and levels of NPK fertilizers on dry matter accumulations and yield performance of foxtail millet (Setaria italica L. Beauv.) - Hasan, MS; Rashid, MH; Rahman, QA; Al-Mamun, MH (Bangladesh Journal of Agricultural Research, 2014)
A study was carried out in the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh, Old Brahmaputra Flood Plains Soil (AEZ-9) during December 2001 to April 2002 to find out the effect of seed rates and NPK levels on dry matter accumulation and grain yield of foxtail millet (Setaria italica L. Beauv.). Four seed rates viz., 8,10,12, and 14 kg/ha and five levels of NPK fertilizers viz., N0P0K0, N10P8K5, N20P16K10, N30P24K15, and N40P32K20 were included in a split plot design with three replications. Dry matter accumulation pattern was determined by harvesting 10 plants randomly at 30, 60, 80, and 102 DAS (days after swing). The yield and yield contributing characters of foxtail millet were influenced by seed rates and NPK levels except tillers per plant and 1000-grain weight significantly. Generally its production rate was 0.86 t/ha when it was grown in char lands in sandy loam soils, the highest grain yield (1.62 t/ha) was produced by 10 kg seeds/ha, which was identical with 12 kg seeds/ha. In case of NPK levels, the treatment was N30P24K10. In case of interaction, the treatment combination 12 kg seeds/ha and N30P24K15 produced the highest grain yield (1.77 t/ha. In case of interaction, the treatment combination 12 kg seeds/ha and N,sub>30P24K15/ha gave the highest grain yield. DOI: http://dx.doi.org/10.3329/bjar.v38i4.19661 Bangladesh J. Agril. Res. 38(4): 689-704, December 2013